1997
DOI: 10.1074/jbc.272.43.27338
|View full text |Cite
|
Sign up to set email alerts
|

An Oxidative Damage-specific Endonuclease from Rat Liver Mitochondria

Abstract: Reactive oxygen species have been shown to generate mutagenic lesions in DNA. One of the most abundant lesions in both nuclear and mitochondrial DNA is 7,8-dihydro-8-oxoguanine (8-oxoG). We report here the partial purification and characterization of a mitochondrial oxidative damage endonuclease (mtODE) from rat liver that recognizes and incises at 8-oxoG and abasic sites in duplex DNA. Rat liver mitochondria were purified by differential and Percoll gradient centrifugation, and mtODE was extracted from Triton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(85 citation statements)
references
References 47 publications
0
84
0
1
Order By: Relevance
“…Monoamine oxidase activity was located in the outer membrane fraction whereas the majority of the malate dehydrogenase activity was detected in the matrix fraction (Table 1). A similar overflow of marker enzyme activities were found present in the sub-mitochondrial preparations of others (38) and may be due in part to the presence of other enzymes utilizing the substrates. Nevertheless, the location of the marker enzymes showed that the fractionation was effective.…”
Section: A/8-oxog Mismatch Binding Activity Is Located In the Mitochomentioning
confidence: 50%
See 1 more Smart Citation
“…Monoamine oxidase activity was located in the outer membrane fraction whereas the majority of the malate dehydrogenase activity was detected in the matrix fraction (Table 1). A similar overflow of marker enzyme activities were found present in the sub-mitochondrial preparations of others (38) and may be due in part to the presence of other enzymes utilizing the substrates. Nevertheless, the location of the marker enzymes showed that the fractionation was effective.…”
Section: A/8-oxog Mismatch Binding Activity Is Located In the Mitochomentioning
confidence: 50%
“…It has been shown that DNA lesions caused by oxidative damage, in particular 8-oxoG, induced in Chinese hamster ovary cells are rapidly removed from the mitochondrial genome suggesting the presence of a 8-oxoG glycosylase/AP lyase (OGG1) (37). Croteau et al partially purified a 25-30 kDa base excision endonuclease that preferentially cleaved C/8-oxoG mismatches but not A/G or A/8-oxoG (38). These OGG1 or MutM-like activities are consistent with several processed forms of OGG1 enzyme being localized to the mitochondrion from a single gene (39).…”
Section: Introductionmentioning
confidence: 62%
“…Mitochondrial BER has been demonstrated by numerous groups and shown to target oxidatively modified DNA bases, such as 8-oxoG and thymine glycol (29)(30)(31)(32)(33)(34)36,37). DNA repair enzymes isolated from mitochondria include several types of damage-specific DNA glycosylases (36)(37)(38)(39), AP endonuclease (40), and DNA ligase (41,42).…”
Section: Mitochondrial Dna Damage and Repairmentioning
confidence: 99%
“…DNA repair enzymes isolated from mitochondria include several types of damage-specific DNA glycosylases (36)(37)(38)(39), AP endonuclease (40), and DNA ligase (41,42). DNA glycosylases that are expressed as nuclear and mitochondrial isoforms encoded by the same gene, include uracil DNA-glycosylase (UDG) (43), and 8-oxoG DNA glycosylase/AP lyase (OGG) (44).…”
Section: Mitochondrial Dna Damage and Repairmentioning
confidence: 99%
“…Several other repair enzymes have been detected in mammalian mitochondda, including a methyltransferase (134), an AP endonuclease (159), and an 8-oxo-dG glycosylase termed mtODE, for mitochondrial oxidative damage endonuclease (160). The latter enzyme excises 8-oxo-dG when it is paired with dC, but not when it is paired with dA.…”
Section: Mitochondrial Repair Proteinsmentioning
confidence: 99%